Properties of particle-reinforced titanium matrix composites produced by powder metallurgy—current research - Vitus Mwinteribo Tabie (Journal of Engineering and Applied Science)
Abstract Particle-reinforced titanium matrix composites (TMCs) have been an area of active research in recent times. This is because of their high specific strength, excellent mechanical properties, and aversion to corrosion which makes them ideal for aerospace, automotive, and biomedical applications. The mechanical and physical properties of TMCs rely on the reinforcement phases and the processing route. Carbides, borides, nitrides, oxides, silicides, and graphene/carbon-matrix reinforcements for TMCs are broadly adopted. Powder metallurgy (PM) is a widely used method for the production of TMCs. This study reviews the common particles that are used as reinforcements in TMCs, their properties, production, the PM techniques used for consolidating them in TMCs, and their effect on the TMCs produced. Current literature and developments in TMCs have also been considered in this review.